2014
DOI: 10.1021/jp5046063
|View full text |Cite
|
Sign up to set email alerts
|

Production of B Atoms and BH Radicals from B2H6/He/H2 Mixtures Activated on Heated W Wires

Abstract: B atoms and BH radicals could be identified by laser-induced fluorescence when B2H6/He/H2 mixtures were activated on heated tungsten wires. The densities of these radical species increased not only with the wire temperature but also with the partial pressure of H2. The densities in the presence of 0.026 Pa of B2H6 and 2.6 Pa of H2 were on the order of 10(11) cm(-3) both for B and BH when the wire temperature was 2000 K. Densities in the absence of a H2 flow were much smaller, suggesting that the direct product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 43 publications
3
30
1
Order By: Relevance
“…Mass spectrometric measurements showed that its decomposition efficiency is 86% when the wire temperature is 2.23 × 10 3 K and the decomposition efficiency increases even more with the addition of H 2 . These efficiencies are higher than those for B 2 H 6 , which has an efficiency of around 70% at 2.0 × 10 3 K and depends little on the wire temperature over this temperature [3,4]. However, since the vapor pressure of H 3 NBH 3 , ∼0.01 Pa at room temperature, is much lower than that of B 2 H 6 , it is necessary to ascertain that a high enough amount of active species, such as B atoms, is produced from H 3 NBH 3 .…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…Mass spectrometric measurements showed that its decomposition efficiency is 86% when the wire temperature is 2.23 × 10 3 K and the decomposition efficiency increases even more with the addition of H 2 . These efficiencies are higher than those for B 2 H 6 , which has an efficiency of around 70% at 2.0 × 10 3 K and depends little on the wire temperature over this temperature [3,4]. However, since the vapor pressure of H 3 NBH 3 , ∼0.01 Pa at room temperature, is much lower than that of B 2 H 6 , it is necessary to ascertain that a high enough amount of active species, such as B atoms, is produced from H 3 NBH 3 .…”
Section: Introductionmentioning
confidence: 67%
“…The experimental procedure and apparatus for this study were similar to those described elsewhere [3,4]. H 3 NBH 3 was effused into a cylindrical chamber from its reservoir, since its vapor pressure is low, on the order of 0.01 Pa at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations